2016
DOI: 10.5812/atr.32915
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Deep Venous Thrombosis Following Orthopaedic Trauma Surgery: An Analysis of 56,000 patients

Abstract: Background:Deep venous thrombosis (DVT) and pulmonary embolism (PE) are recognized as major causes of morbidity and mortality in orthopaedic trauma patients. Despite the high incidence of these complications following orthopaedic trauma, there is a paucity of literature investigating the clinical risk factors for DVT in this specific population. As our healthcare system increasingly emphasizes quality measures, it is critical for orthopaedic surgeons to understand the clinical factors that increase the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Advanced age >70 years, female sex, obesity, and hypertension have been known as risk factors of VTE after TKA . In this study, platelet aggregation ≥40% was more frequently observed in patients with VTE, while the incidences of these risk factors were not significantly higher.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Advanced age >70 years, female sex, obesity, and hypertension have been known as risk factors of VTE after TKA . In this study, platelet aggregation ≥40% was more frequently observed in patients with VTE, while the incidences of these risk factors were not significantly higher.…”
Section: Discussionmentioning
confidence: 44%
“…Advanced age >70 years, female sex, obesity, and hypertension have been known as risk factors of VTE after TKA. 6,15 Prior clinical studies observed that WBC and platelet counts are correlated with increased platelet aggregation in arterial thrombotic events. 19,20 In the present study, the incidence of previous arterial thrombotic events such as CAD and IS, WBC count, and platelet count showed no significant difference among the aggregation groups, although it was lower in the low aggregation group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…thrombosis In these patients, suggested to be associated with injury of vascular wall, immobility, and activated coagulation pathways. 21 (c) Trauma. higher Incidence of DVT is seen in patients with lower extremity fractures compared to those with trauma at other sites, such as the abdomen, face or thorax.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic surgical procedures may carry increased risk for the development of VTE due to temporary endothelial dysfunction at the operation site, venous stasis as a result of patient immobilization during the recovery period and possible hypercoagulability state which is also patient dependent [ 5 ]. According to the American College of Chest Physicians (ACCP), there is no validated tool to assess individual risk factors and their contribution to the development of VTE in patients undergoing orthopaedic procedures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%